ANALISIS RASIO PROFITABILITAS DAN RASIO AKTIVITAS SEBAGAI DASAR PENILAIAN KINERJA KEUANGAN PADA PERCETAKAN DI TANJUNGPINANG (STUDI KASUS CV. BINTAN AZIZI) - Salihi Salihi; Nurlina Azis; Hasnarika (Bajang Institute, 2023)
The purpose of this study was to determine the financial performance of CV. Bintan Azizi in the period 2019-2021 which is seen based on profitability ratios and activity ratios as well as performance assessments based on Kasmir industry standards (2015). The method used in this research is qualitative method. The object of the research is the financial statements of CV. Bintan Azizi. The type of data used in this research is secondary data and the data collection technique in this study is to use the interview method and the library method. The results of this study indicate that CV. Bintan Azizi when viewed from the gross profit margin is said to be very good because the average value of 62% is above the industry standard, from the net profit margin it is said to be very good because the average value of 39% is above the industry standard and the return on investment is also said to be good because the average value is 26% which is still in the good category of industry standards. Meanwhile, based on the activity ratio, CV. Bintan Azizi has not been able to manage its assets, it can be seen from the highest average receivable turnover of only 5 times which is far below the industry standard, from inventory turnover the average value is only 1 time which is far below the industry standard and for total assets turnover is said to be sufficient because the average value is 1 times which is close to the industry standard. It can be concluded that the profitability ratios and activity ratios are very helpful for companies to be able to find out how the company's financial performance is, and can also find out the use of resources and control costs used as well as effective and efficient sales levels